Digital payments and consumption: Evidence from the 2016 demonetization in India - AGARWAL, Sumit (Institutional Knowledge at Singapore Management University, 2024)
We study how consumer spending responds to digital payments, using the differential switch to digital payments across consumers induced by the sudden 2016 Indian Demonetization for identification. Usage of digital payments rose by 3.38 percentage points and monthly spending increased by 3% for an additional 10 percentage points in prior cash dependence. Spending remained elevated even when cash availability recovered. Robustness analyses show that the spending response is not driven by income shocks, credit supply, price changes, or consumers' moving to the formal market. We provide evidence that digital payments increase consumer spending due to subdued salience.